The Role of Visual Design Content Quality, and System Users in Improving the Net Benefits of Electronic Medical Records in Hospital X - Dede Cintia Dianni Martin; Anastina Tahjoo; Endang Ruswanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The implementation of Electronic Medical Records (RME) in hospitals often faces various obstacles that hinder the achievement of maximum benefits. The main problems lie in the visual design, content quality, and user acceptance of the system, which have an impact on the work efficiency of medical personnel and the quality of service to patients. This study aims to analyze the effect of visual design and content quality of RME on Net benefits by considering system users as intervening variables. This research approach uses the HOT-Fit model that integrates human, organizational, and technological dimensions, accompanied by EUCS theory to assess visual and content quality and UTAUT theory to understand user perceptions. The results showed that the dimensions of visual design and content quality had a significant influence on the Net benefits of RME, both directly and through intervening system user variables. The findings also revealed that weaknesses in menu structure and information relevance hindered system performance, although overall, the Net benefits of RME were in the high category. Therefore, continuous evaluation and improvement on visual aspects, such as a more intuitive layout, as well as more organized and relevant content, are priorities for improving RME implementation. Key suggestions include optimizing the menu structure, simplifying navigation, integrating the system across hospital units, and providing ongoing training for system users. Thus, this study contributes to the development of a more effective RME implementation strategy, so as to support digital transformation in the healthcare sector.